The effectiveness of children television program in improving children's language proficiency: a study on Didi and Friends / Farahani Mohd Asli ... [et al.] - Mohd Asli, Farahani; Ghazali, Nur Azmina; Zuhaizar, Anis Athirah; Abdul Malek, Siti Sarah; Mohd Nasir, Muhammad Saiful Adli
The purpose of this study is to identify the effectiveness of children television program in improving children's language proficiency, a study on Didi and Friends. This program is one of the well-known children television program in Malaysia and Asia countries that is use to entertain and at the same time educate the children. The researchers conducted an in-depth interview with four informants which consisted of three kindergarten teachers from Taska Johan Bistari and a pediatric at Senawang Child Specialist Clinic based on purposive sampling. The data was analyse using thematic analysis. From the overall research, it can be concluded that the children do improve their language proficiency through the animation element of the program, the children can react positively toward Didi and Friends. However, the children can still learn and develop their language proficiency even without watching Didi and Friends.